Mapping Violeta Parra's Cultural Landscapes (Springer International Publishing, 2018)
"Readers discovering Violeta Parra for the first time and those who wish to deepen their understanding of her will appreciate this illuminating book." -Nancy Morris, Professor, Department of Media Studies and Production, Temple University, USA "The editor and her collaborators have given us a gift-the ability to 'listen' differently to the music and art that embodied a nation, a social era, and a singular artist." -Steve J. Stern, Alberto Flores Galindo and Hilldale Professor of History, Emeritus, University of Wisconsin-Madison, USA One of the leading figures in Latin American folk music and art during her lifetime, Violeta Parra was a vital force in the artistic, musical, visual, cultural, and social cultural production of the Chilean 1960s. Fifty years after her death, she continues to deeply influence artists of the present day. This book revisits Parra's work and legacy to illustrate her global impact across artistic and political boundaries. Contributors offer multi-disciplinary perspectives that delineate how Parra contributed to shaping and-at the same time-antagonizing, societal processes in mid-20th century Chile. Patricia Vilches is Professor of Spanish and Italian and Scholar in Residence at Harlaxton College, UK and Professor of Spanish and Italian at Lawrence University, USA (retired). She is author of Blest Gana via Machiavelli and Cervantes: National Identity and Social Order in Chile (2017) and co-editor of Seeking Real Truths: Multidisciplinary Perspectives on Machiavelli (2007).